IMPROVING THE QUALITY OF OIL PALM CULTIVATION WITH GOOD AGRICULTURAL PRACTICES (GAP) AND GOOD HANDLING PRACTICES (GHP) FOR SUPPORTING ISPO IN KUALA PESISIR DISTRICT NAGAN RAYA REGENCY - Aswin Nasution; Abdul Latif; Bagio; Muhammad Jalil; Qhisthina Atikah; Sri Handayani; Akhmad Baihaqi; Rusdi Faizin (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
Nagan Raya District, with an area of 52,228 hectares of oil palm plantation with CPO production of 98,620 tons in 2023 (Plantation Office of Nagan Raya District, 2023). These plantations are managed by large companies and smallholders who are members of cooperatives or farmer groups, making it the main economic sector in the area. The development of Nagan Raya's oil palm plantations, continues to increase thanks to the replanting program conducted by the government and the private sector to replace old plants with superior seedlings that are more productive and disease-resistant. The implementation of better agricultural practices, such as Good Agricultural Practices (GAP) and Good Handling Practices (GHP), also plays an important role in improving productivity and crop quality. The training was conducted over two days, on September 10-11, 2024, at the Kuala Pesisir sub-district Vocational Training Center (BLK). The training method included detailed material explanations and discussion sessions. The materials were delivered systematically using real-life examples to facilitate participants' understanding. GAP and GHP training is necessary for farmers in Kuala Pesisir sub-district to improve the productivity and quality of fresh fruit bunches (FFB) and to preserve the environment. The training supports compliance with certification standards such as the Indonesian Sustainable Palm Oil (ISPO), which opens access to global markets and increases the competitiveness of Indonesian palm oil products. The training ensures that all palm oil businesses meet permitted agricultural standards, including sustainable cultivation practices and good environmental management. So that palm oil products are recognized as sustainable and environmentally friendly products in accordance with ISPO standards. In addition, improving the welfare of oil palm farmers will support them in better providing for their families. Prosperous farmers are not only able to fulfill their daily needs but also contribute to the region and country.